FAM134B-mediated endoplasmic reticulum autophagy protects against cisplatin-induced spiral ganglion neuron damage - Wang, Fan; Xu, Yue; Wang, Yajie; Liu, Qian; Li, Yanan; Zhang, Weiwei; Nong, Huiming; Zhang, Junhong; Zhao, Hao; Yang, Huaqian; Guo, Lingchuan; Li, Jianfeng; et al. (Frontiers in Pharmacology, 2025)
IntroductionCochlear spiral ganglion neurons (SGNs) could be damaged by ototoxic drug, cisplatin (Cis), during which process autophagy was involved. FAM134B, the first detected endoplasmic reticulum autophagy (ER-phagy) receptor, plays an important part in the dynamic remodelling of the ER, the mutation of which affects sensory and autonomic neurons. However whether FAM134B-mediated ER-phagy involved in Cis-induced SGN damage or not was unknown. The present study was designed to determine whether FAM134B is expressed in SGNs of C57BL/6 mice and, if so, to explore the potential function of FAM134B in Cis-induced SGN damage in vitro.MethodsMiddle turns of neonatal murine cochleae were cultured and treated with 30 μM Cis in vitro. The distribution of FAM134B, morphological changes of SGNs, and the colocalization of ER segments with lysosomes were measured by immunofluorescence (IF). Apoptosis was measured by TUNEL staining. The expression of FAM134B, proteins associated with ER stress, autophagy and apoptosis was measured by western blot. The reactive oxygen specie (ROS) levels were evaluated by MitoSOX Red and 2′,7′-Dchlorodihydrofluorescein diacetate (DCFH-DA) probe. Anc80-Fam134b shRNA was used to knockdown the expression of FAM134B in SGNs.ResultsWe first found the expression of FAM134B in the cytoplasm of SGNs, especially in the fourth postnatal day mice. Results showed decreases in the number of SGNs and FAM134B expression, as well as increases of ROS level, ER stress, ER-phagy, and apoptosis after Cis stimulus. Inhibiting autophagy increased the expression of FAM134B, and aggravated Cis-induced SGN damage, while the opposite changes were observed when autophagy was activated. Additionally, co-treatment with the N-Acetyl-L-Cysteine (NAC), ROS scavenger, alleviated Cis-induced ER stress, ER-phagy, and apoptosis. What’s more, knockdown the expression of FAM134B in SGNs made SGNs more vulnerable to cisplatin-induced injury.DiscussionThe present study revealed the expression pattern of FAM134B in C57BL/6 murine SGNs for the first time. Moreover, our work further verified the protective function of FAM134B mediated by ER-phagy in Cis-induced SGN apoptosis, at least partially, correlated with the accumulation of ROS and induction of ER stress, though the detailed regulatory mechanism through which needs much more work to reveal.